Midterm Follow-Up of Patients with Perioperative Myocardial Infarction after Coronary Artery Bypass Surgery: Clinical Significance of Different Treatment Strategies - Alexiou, Konstantin; Wilbring, Manuel; Koch, Christian; Kappert, Utz; Tugtekin, Sems; Matschke, Klaus (The Thoracic and Cardiovascular Surgeon, 2012)
Background The purpose of the study was to analyze the causes of postoperative myocardial infarction (PMI) and the impact of different treatment strategies on (1) postoperative outcome, (2) major adverse events (MACE), and (3) postoperative Canadian Cardiovascular Society (CCS) at 3-year follow-up.Patients Between May 2001 and July 2006, 113 patients with PMI were categorized in three groups: (A) conservative therapy (50 patients); (B) percutaneous coronary intervention (PCI) (25 patients), and (C) re-CABG (38 patients).Results Overall in-hospital mortality was 7.1% (n = 8), being 10.0% in group A (n = 5), 4.0% in group B (n = 1) and 5.3% (n = 2) in group C (p = n.s.), respectively. The cumulative survival rates at 3 years were 90% for group A, 92% for group B, and 89.5% for group C (p = n.s). The MACE rate at 3-year follow-up for all patients was 27.4% and was significantly higher in group A (34%) and group B (36%) compared with group C (13.2%) (p = 0.05). Mean CCS was significantly reduced at follow-up in the groups compared with the preoperative angina class. However, group B and C showed a significant improvement in CCS compared with group A (p = 0.044/p < 0.001). Further group C was superior to group B (p = 0.032).Conclusion At 3 years of follow-up, this study showed no survival benefits from any therapeutical procedure; however patients treated with re-CABG had better freedom from repeat revascularization procedures and from MACCE. In addition, the conservative and PCI group had a higher incidence of recurrence of angina.
Keywords: cardiac catheterization/intervention (incl. PCI); coronary artery bypass; grafts surgery; CABG; intensive care; myocardial infarction (includes complications; e.g., rupture)